ARWANA FISH BATIK MOTIF IN CASUAL CLOTHES - Desinta, Vania Vicky (Indonesian Institute of the Arts Surakarta, 2023)
Arowana fish, a protected species due to its dwindling population, became the inspiration for this work. The aims of this work are: (1) to develop a batik motif design inspired by the arowana fish; (2) designing casual clothes with arowana fish batik motifs; and (3) the use of arowana fish-inspired batik motifs on casual clothing. SP Gustami's theory is used in the work production process, which consists of three stages of six steps: investigation, design, and embodiment. The investigation stage includes finding as much information as possible about the arowana. The design stage comes next, when many factors are taken into account, including functional characteristics, materials, processes, aesthetics and ergonomics. The embodiment step, which involves turning a design into a work, is the final phase. The dab method using Remasol dye is used for colorin fish g. The final product consists of four casual wear items with the names Antarrazka, Sraddha, Upeksha and Antarsukha. The design is inspired by arowana fish.